2012
DOI: 10.2337/dc11-1825
|View full text |Cite|
|
Sign up to set email alerts
|

25-Hydroxyvitamin D Concentrations and In Vivo Insulin Sensitivity and β-Cell Function Relative to Insulin Sensitivity in Black and White Youth

Abstract: OBJECTIVETo examine the relationships between plasma 25-hydroxyvitamin D [25(OH)D] and in vivo insulin sensitivity and β-cell function relative to insulin sensitivity, disposition index (DI), in black and white youth.RESEARCH DESIGN AND METHODSPlasma 25(OH)D concentrations were analyzed in banked specimens in healthy youth aged 8 to 18 years who had existing data on hyperinsulinemic-euglycemic and hyperglycemic clamp to assess insulin sensitivity and secretion, and measurements of body composition, and abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 26 publications
5
40
1
Order By: Relevance
“…The potential effects of VitD on glucose homeostasis are considered to be mediated by autocrine and paracrine functions involving the transcriptional regulation of genes in pancreatic b-cells, skeletal myocytes and immune cells, improving insulin secretion and sensitivity and reducing inflammation (13,16) . Despite theoretical links between VitD and insulin sensitivity and/or secretion, controversy remains regarding the relationship between 25(OH)D levels and surrogate indices of insulin sensitivity (4)(5)(6)(7)25,26) or b-cell function (7,25,26) and the risk of glucose intolerance or T2DM (6,9,27) . These discrepancies in the relationships between VitD status and outcomes related to glucose homeostasis in paediatric or adult populations may be attributable to differences in study sample size, participant characteristics (race, ethnicity and degree of obesity), method of measuring insulin sensitivity and/or b-cell function, and the adjusted markers of adiposity used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential effects of VitD on glucose homeostasis are considered to be mediated by autocrine and paracrine functions involving the transcriptional regulation of genes in pancreatic b-cells, skeletal myocytes and immune cells, improving insulin secretion and sensitivity and reducing inflammation (13,16) . Despite theoretical links between VitD and insulin sensitivity and/or secretion, controversy remains regarding the relationship between 25(OH)D levels and surrogate indices of insulin sensitivity (4)(5)(6)(7)25,26) or b-cell function (7,25,26) and the risk of glucose intolerance or T2DM (6,9,27) . These discrepancies in the relationships between VitD status and outcomes related to glucose homeostasis in paediatric or adult populations may be attributable to differences in study sample size, participant characteristics (race, ethnicity and degree of obesity), method of measuring insulin sensitivity and/or b-cell function, and the adjusted markers of adiposity used.…”
Section: Discussionmentioning
confidence: 99%
“…We used HOMA-IR and QUICKI, reflecting only hepatic insulin sensitivity rather than in vivo whole-body insulin sensitivity, which encompasses both hepatic and peripheral tissues, measured using hyperinsulinaemic-euglycaemic and hyperglycaemic clamps. Rajakumar et al (26) recently reported that 25(OH)D levels are not independently related to in vivo insulin sensitivity or b-cell function, after adjustment for total body fat or visceral adipose tissue, in healthy black and white youth aged 8-18 years without dysglycaemia. Our study is the first to show that a low VitD status is significantly related to hepatic IR and IFG, independently of total body fat, in Korean adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Hypovitaminosis D is associated with obesity (2), and low vitamin D states predict higher fasting glycemia and insulin resistance in population studies (3,4), yet other studies showed no relations between vitamin D status and glucose homeostasis after adjusting for adiposity (5,6). Vitamin D supplementation has not consistently benefited glycemia in intervention trials despite adequate increments into a "normal range" (7).…”
mentioning
confidence: 99%
“…Although our sample size is relatively small, some larger studies have similarly reported a lack of association between 25-OHD and glucose homeostasis, 5,14 arguing instead that apparent relationships are confounded by body fat, which demonstrates a strong inverse association with circulating 25-OHD. 13,14 Of note, associations of the ratio of PTH/25-OHD 17,23 with insulin measures were stronger than those of PTH alone within obese girls, suggesting a possibly additional, albeit minor, role of lower 25-OHD levels in driving these associations. Thus, further research is needed to investigate associations between 25-OHD and insulin sensitivity independent of fat stores across the weight spectrum.…”
Section: Discussionmentioning
confidence: 79%